APPLICATION OF THE METHOD OF LAGRANGE’S UNDETERMINED MULTIPLIERS IN DETERMINATION OF OPTIMAL REACTIVE POWER COMPENSATION - Соломчак, Олег; Романюк, Юрий (Modern engineering and innovative technologies, 2017)
We consider the method of selecting the type and optimum reactive power sources to compensate for reactive load of oil and gas industry customers according to the criterion of minimum discounted costs which include the costs of generation and transmission